A cleansing effect through the right to information - Rao, P. Mohan; Murthy, C.G.K. (2009)
Modern democracy involves a wider and direct concept of accountability. The trend is towards accountability in terms of standards of performance and service delivery of public agencies to the citizens they are expected to serve. Accountability is possible only when public have access to information relating to the functioning of those agencies. Transparency and openness in functioning have a cleansing effect on the operation of these agencies. It goes without saying, the right to information will be an important aid in ensuring transparent administration of public affairs and will help expose corruption and nepotism to ensure a clean administration. It will strengthen the mechanism of accountability of those using public funds and exercising public power. - Reproduced.
Keywords: Right to information